Chave's memories = Los recuerdos de Chave - Delgado, María Isabel (Piñata Books, 1996)
A woman recalls childhood visits to her grandparents' ranch in Mexico, where she and her brother played with her cousins and listened to the stories of an old Indian ranch hand.